A New Optical Fiber Probe-Based Quantum Dots Immunofluorescence Biosensors in the Detection of Staphylococcus aureus - Cui, Jiewei; Zhou, Minjuan; Li, Ying; Liang, Zhixin; Li, Yanqin; Yu, Ling; Liu, Yang; Liang, Yuan; Chen, Liangan; Yang, Changxi (Frontiers in Cellular and Infection Microbiology, 2021)
Staphylococcus aureus (S. aureus) is one of the most common clinical pathogenic bacteria with strong pathogenicity and usually leads to various suppurative infections with high fatality. Traditional bacterial culture for the detection of S. aureus is prone to diagnosis and antimicrobial treatment delays because of its long-time consumption and low sensitivity. In this study, we successfully developed a quantum dots immunofluorescence biosensor for S. aureus detection. The biosensor combined the advantages of biosensors with the high specificity of antigen-antibody immune interactions and the high sensitivity and stability of quantum dots fluorescence. The results demonstrated that the biosensor possessed high specificity and high sensitivity for S. aureus detection. The detection limit of S. aureus reached 1×104 cfu/ml or even 1×103 cfu/ml, and moreover, the fluorescence intensity had a significant positive linear correlation relationship with the logarithm of the S. aureus concentration in the range of 103 107 cfu/ml (correlation coefficient R2=0.9731, P=0.011). A specificity experiment showed that this biosensor could effectively distinguish S. aureus (1×104 cfu/ml and above) from other common pathogenic (non-S. aureus) bacteria in nosocomial infections, such as Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii and Escherichia coli. Additionally, the whole detection procedure spent only 2 hours. In addition, the biosensor in this study may not be affected by the interference of the biofilm or other secretions since the clinical biological specimens are need to be fully liquefied to digest and dissolve viscous secretions such as biofilms before the detection procedure of the biosensor in this study. In conclusion, the biosensor could meet the need for rapid and accurate S. aureus detection for clinical application.